Obese Individuals with and without Type 2 Diabetes Show Different Gut Microbial Functional Capacity and Composition - Thingholm, Louise B; Rühlemann, Malte C; Koch, Manja; Fuqua, Brie; Laucke, Guido; Boehm, Ruwen; Bang, Corinna; Franzosa, Eric A; Hübenthal, Matthias; Rahnavard, Ali; Frost, Fabian; Lloyd-Price, Jason; et al. (Cell host & microbe, 2019)
Obesity and type 2 diabetes (T2D) are metabolic disorders that are linked to microbiome alterations. However, their co-occurrence poses challenges in disentangling microbial features unique to each condition. We analyzed gut microbiomes of lean non-diabetic (n = 633), obese non-diabetic (n = 494), and obese individuals with T2D (n = 153) from German population and metabolic disease cohorts. Microbial taxonomic and functional profiles were analyzed along with medical histories, serum metabolomics, biometrics, and dietary data. Obesity was associated with alterations in microbiome composition, individual taxa, and functions with notable changes in Akkermansia, Faecalibacterium, Oscillibacter, and Alistipes, as well as in serum metabolites that correlated with gut microbial patterns. However, microbiome associations were modest for T2D, with nominal increases in Escherichia/Shigella. Medications, including antihypertensives and antidiabetics, along with dietary supplements including iron, were significantly associated with microbiome variation. These results differentiate microbial components of these interrelated metabolic diseases and identify dietary and medication exposures to consider in future studies.